Interspecific Variation in Susceptibility to Insecticides by Lepidopteran Pests of Soybean, Cotton, and Maize Crops from Brazil - MacHado E.P. (2022)
© 2022 The Author(s) 2022.The interspecific variation in susceptibility to insecticides by lepidopteran species of soybean [Glycine max L. (Merr.)], cotton (Gossypium hirsutum L.), and maize (Zea mays L.) crops from Brazil were evaluated. Populations of Anticarsia gemmatalis (Hübner) (Lepidoptera: Erebidae), Chrysodeixis includens (Walker), Helicoverpa armigera (Hübner), Spodoptera frugiperda (Smith), Spodoptera eridania (Stoll), Spodoptera cosmioides (Walker), and Spodoptera albula (Walker) (Lepidoptera: Noctuidae) were collected from 2019 to 2021. Early L3 larvae (F2 generation) were exposed to the formulated insecticides methoxyfenozide, indoxacarb, spinetoram, flubendiamide, and chlorfenapyr in diet-overlay bioassays. The median lethal concentrations (LC50) were used to calculate tolerance ratios (TR) of each species in relation to the most susceptible species to each insecticide. The lowest LC50 values were verified for A. gemmatalis to all insecticides tested. Chrysodeixis includens and most of the Spodoptera species were moderately tolerant to methoxyfenozide (TR < 8.0-fold) and indoxacarb (TR < 39.4-fold), whereas H. armigera was the most tolerant species to methoxyfenozide (TR = 21.5-fold), and indoxacarb (TR = 106.4-fold). Spodoptera cosmioides, S. eridania, and S. albula showed highest tolerance to spinetoram (TR > 1270-fold), S. eridania, S. frugiperda, and S. albula to flubendiamide (TR from 38- to 547-fold), and S. albula to indoxacarb (TR = 138.6-fold). A small variation in susceptibility to chlorfenapyr (TR < 4.4-fold) was found among the lepidopteran evaluated. Our findings indicate a large variation in susceptibility to indoxacarb, spinetoram, and flubendiamide and a relatively low variation in susceptibility to methoxyfenozide and chlorfenapyr by lepidopteran species of soybean, cotton, and maize from Brazil.